Soft Neurological Signs in Malnourished Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The relation of abnormal soft neurologic signs and EEG abnormalities to the severity of malnutrition was investigated in 208, 8-10 year old male school children at the Nutrition Section, Department of Paediatrics, and the Section of Neurology, Department of Medicine, Institute of Medical Sciences, Banaras Hindu University, Varanasi, India.